By-Laws and Ordinances of the City of Pittsburgh 73 (1828) - (:unkn) unknown (My University, 1816)
Ch. 2, §§ 1-3 : That no shop-keeper or other person or persons, shall keep, at the same time, in any house, shop, cellar or warehouse, or other apartment, or in any boat within the said city, more than thirty pounds weight of gun-powder. § 2. That the aforesaid quantity of gun-powder allowed to be kept within the city, shall be deposited in a place by itself, separate from other goods and commodities, and shall be secured by lock and key, or in some other safe manner. § 3. That no person shall carry or convey in any dray, cart, wagon or other carriage, any greater quantity of gun-powder than thirty pounds weight, at any one time, in or through the city, without securing the same in a good bag or bags, or within a canvas or other safe covering completely around the said powder, sufficient to prevent the same from scattering from the said carriage.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER